Encapsulation of Amikacin into Microparticles Based on Low-Molecular-Weight Poly(lactic acid) and Poly(lactic acid-co-polyethylene glycol) - Glinka, Marta; Filatova, Katerina; Kucińska-Lipka, Justyna; Bergerova, Eva Domincova; Wasik, Andrzej; Sedlařík, Vladimir (Molecular pharmaceutics, 2021)
The aim of this study was to fabricate novel microparticles (MPs) for efficient and long-term delivery of amikacin (AMI). The emulsification method proposed for encapsulating AMI employed low-molecular-weight poly(lactic acid) (PLA) and poly(lactic acid-co-polyethylene glycol) (PLA-PEG), both supplemented with poly(vinyl alcohol) (PVA). The diameters of the particles obtained were determined as less than 30 μm. Based on an in-vitro release study, it was proven that the MPs (both PLA/PVA- and PLA-PEG/PVA-based) demonstrated long-term AMI release (2 months), the kinetics of which adhered to the Korsmeyer-Peppas model. The loading efficiencies of AMI in the study were determined at the followings levels: 36.5 ± 1.5 μg/mg for the PLA-based MPs and 106 ± 32 μg/mg for the PLA-PEG-based MPs. These values were relatively high and draw parallels with studies published on the encapsulation of aminoglycosides. The MPs provided antimicrobial action against the Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae bacterial strains. The materials were also comprehensively characterized by the following methods: differential scanning calorimetry; gel permeation chromatography; scanning electron microscopy; Fourier transform infrared spectroscopy-attenuated total reflectance; energy-dispersive X-ray fluorescence; and Brunauer-Emmett-Teller surface area analysis. The findings of this study contribute toward discerning new means for conducting targeted therapy with polar, broad spectrum antibiotics.
Keywords: nosiče léků; Molecular Weight; Drug Carriers; Polyvinyl Alcohol; laktáty; Anti-Bacterial Agents; microparticles; targeted therapy; molekulová hmotnost; Klebsiella pneumoniae; poly(lactic acid); polyestery; Drug Compounding; Capsules; Microbial Sensitivity Tests; Polyethylene Glycols; drug delivery systems; Staphylococcus aureus; polyethylenglykoly; velikost částic; Pseudomonas aeruginosa; Escherichia coli; Amikacin; příprava léků; amikacin; Lactates; polyvinylalkohol; Drug Liberation; antibakteriální látky; uvolňování léčiv; Polyesters; tobolky; amikacin encapsulation; Solubility; mikrobiální testy citlivosti; rozpustnost; Particle Size